Labor Market and Globalization: A Comparison of the Latin American and the East Asian Experiences in the 1980s and 1990s - Randolph Luca Bruno (Institute for the Study of Labor (IZA), 2010)
In this paper we analyse the labor market and its relationship with globalization in two groups of countries similar in their GDP per capita levels at the beginning of the 1980s but otherwise significantly different in their economic and social structures. On the one hand we look at Argentina, Brazil and Chile, on the other hand we analyse South Korea, Taiwan and Thailand. It is argued that the Latin American group adopted pro-globalization policies too quickly and without an adequate social safety net, and that the East Asian group was particularly vulnerable to the 1997 crisis in connection with an ill-designed financial markets liberalisation and poor labor market policies. We suggest that the high social costs of labor market imbalances generated throughout the 1980s and 1990s in these two groups of countries should have been tackled within an encompassing development strategy, with an eye at social safety nets and labor supply policies such as active and passive labor market institutions designed for each country specifically.
Keywords: F16; J21; O15; 330; globalization; labor market; Latin America; East Asia; Globalisierung; Schock; Arbeitsmarkt; Arbeitsmarktpolitik; Arbeitsmarktpolitik; Institutionalismus; Vergleich; Argentinien; Brasilien; Chile; Südkorea; Thailand